DAKWAH MULTIKULTURAL DI INDONESIA Studi Pemikiran dan Gerakan Dakwah Abdurrahman Wahid - Rosidi, Rosidi (Analisis: Jurnal Studi Keislaman, 2013)
History records that the process of Islamization in the archipelago lasted peacefully.  It  was under such peaceful  process that made Islam became  the  religion  of the  majority  of people  who   had previuosly embraced Hinduism , Buddhism , and traditional religion.   Some factors that influenced the success of the Islamization  process are identified mainly in the form of cultural approach  rather than the use of  violence and military force.  The recent trend, however, shows that there is a shift in the methods of religious  propaganda.  Many muslim missionaries  tend  to be intolerant,  rigid, self-righteous,  even with their fellow muslims. Some even use violence  such as damaging  a place of worship, or prevent  others  to  worship.  This  study  tries  to   identify  the approaches, methods, and multicultural tendency of Abdurrahman Wahid ( Gus Dur ), who preaches Islam with friendly and peaceful manners by respecting differences and the rights of every person.